The effect organic solvent extract of Datura metel leaves on some biological aspects of Hyalomma schulzei (olenev) (Acari:Ixodidae) - Esraa F. Wathah; Mohamad R. Annon (Al-Qadisiyah Journal of Pure Science, 2017)
The current studay include the investigation of impact organic solventextract(Ethyl alcohol, Ethyl acetate, Hexan ) of Datura metel leaves on immatureand adult stage of the ticks Hyalomma schulzei under laboratory conditions.Biological activity of extracts was determined using different concentrations(10,30,50,70)%. The results showed the followings:Mortality eggs and larvae after exposure to different concetraction to threeSolvent reahed 90% the mortarty of non-feedeing nymphs reached 90%, 77.7%,68.85% and feedeing nymphs reached %83.85 , 72.78 % , 66.14% respectively at theConcentration of 70 mg\ml while mortility rate of adult stage non-feedeingmales90% , 61.22% , 59% and feedeing77.7% , 57% , 51.14% while non-feedeingfemales 72.29%, 53.15% , 46.92% . and the feedeingfemales 63.93%, 51.84%, 40.7atconcentration 70 mg\ml after exposur to previously extract on respectively. Theresult indicated that Ethyalcohol. extracts were more effective than Ethyle acetateand Hexan.